Effect of students’ seminar as a revision strategy in biochemistry among I MBBS students in a medical college in Tamil Nadu - Sivakumar J,; Anitha G,; Dhinesh G, (Asian Journal of Medical Sciences, 2024)
Background: Small group teaching is one of the components of competency-based medical education which was implemented in 2019 by NMC. Seminar is one of the methods of small group teaching which increases the engagement of students, self-directed learning, communication skills, and peer discussion. Aims and Objectives: The present idea is to study the effect of students’ seminar as a revision strategy in Biochemistry among I MBBS students. Materials and Methods: After obtaining the IEC approval, I MBBS students who are 250 in number will be divided into small groups. Each group will be given a particular seminar topic. All the students in the particular group will be instructed to present the topic on random basis. A total of 15 seminars will be conducted on particular topics. Pre-tests and post-tests (immediately after the seminar) will be conducted after the seminars along with pre-test and post-test questionnaires will be obtained and collated to understand how far the student’s acceptance of students’ seminar and its effectiveness. Results: Our study results showed that that there is an increase in the percentage of marks in the post-evaluation and also more than 70% of the students responded positively to most of the queries in the feedback questionnaire. Conclusion: Our study results showed that there is an increase in the percentage of marks in the post-evaluation and also more than 70% of the students responded positively to most of the queries in the feedback questionnaire.